Pengaruh Celebrity Endorser, Brand Image, Dan Kualitas Produk Terhadap Keputusan Pembelian Marina Hand and Body Lotion Mahasiswa Program Sarjana Universitas Diponegoro - Putri Estiningrum; Saryadi Saryadi; Agung Budiatmo (Universitas Diponegoro, 2025)
The cosmetics and beauty industry is currently experiencing rapid growth so the level of competition is very high, one of which is the marina brand. Based on marina top brand index data for 2020-2023, it is fluctuating and sales data for 2019 - 2023 is fluctuating and the target achievement is not met. This research aims to test the influence of the independent variables celebrity endorser, brand image, and product quality on the dependent variable purchasing decisions. The type of research is explanatory research using non-probability sampling techniques with a purposive sampling method of 96 respondents from Diponegoro University Undergraduate Program students who use and make purchasing decisions about Marina hand and body lotion. The data was processed using IBM SPPS Sattistic version 23. The research results showed that celebrity endorsers had a positive and significant influence on purchasing decisions, brand image had a positive and significant influence on purchasing decisions, product quality had a positive and significant influence on purchasing decisions. Simultaneously celebrity endorser, brand image, and product quality have a positive and significant effect on purchasing decisions. Advice that can be given to companies is that they must choose the right celebrity endorser to promote their products, strengthen their branding to create a good brand image in the minds of consumers, and consider the formulation of the ingredients used in the product so that its quality is maintained.Keywords: Celebrity endorser; brand image; product quality; purchase decisionIndustri kosmetik dan kecantikan saat ini mengalami pertumbuhan yang pesat sehingga tingkat persaingannya sangat tinggi, salah satunya adalah brand marina. Berdasarkan data top brand index marina tahun 2020-2023 fluktuatif dan data penjualan selama tahun 2019 - 2023 fluktuatif serta capaian targetnya tidak memenuhi. Penelitian ini bertujuan untuk menguji pengaruh variabel independent celebrity endorser, brand image, dan kualitas produk terhadap variabel dependen keputusan pembelian. Tipe penelitian adalah explanatory research dengan menggunakan teknik non probability sampling dengan metode purposive sampling sebanyak 96 responden Mahasiswa Program Sarjana Universitas Diponegoro yang menggunakan dan melakukan keputusan pembelian Marina hand and body lotion. Data diolah menggunakan SPPS versi 23. Hasil penelitian menunjukan celebrity endorser berpengaruh positif dan signifikan terhadap keputusan pembelian, brand image berpengaruh positif dan signifikan terhadap keputusan pembelian, kualitas produk berpengaruh positif dan signifikan terhadap keputusan pembelian. Secara simultan celebrity endorser, brand image, dan kualitas, produk berpengaruh positif dan signifikan terhadap keputusan pembelian. Saran yang dapat diberikan kepada perusahaan adalah harus memilih celebrity endorser yang tepat untuk memperomosikan produknya, memperkuat brandingnya akan brand image yang tercipta baik dibenak konsumen, dan mempertimbangkan formulasi bahan yang digunakan pada produk agar kualitasnya tetap terjaga. Kata Kunci: Celebrity Endorser; Brand Image; Kualitas Produk; Keputusan Pembelian